2011
DOI: 10.1172/jci57413
|View full text |Cite
|
Sign up to set email alerts
|

Altered chromatin architecture underlies progressive impairment of the heat shock response in mouse models of Huntington disease

Abstract: Huntington disease (HD) is a devastating neurodegenerative disorder for which there are no disease-modifying treatments. Previous studies have proposed that activation of the heat shock response (HSR) via the transcription factor heat shock factor 1 (HSF1) may be of therapeutic benefit. However, the effect of disease progression on the HSR and the therapeutic potential of this pathway are currently unknown. Here, we used a brain-penetrating HSP90 inhibitor and physiological, molecular, and behavioral readouts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
146
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 158 publications
(156 citation statements)
references
References 70 publications
8
146
1
Order By: Relevance
“…Protein lysates were prepared from 4-, 8-, and 14-wk-old R6/2 transgenic mouse brains and wild-type controls and analyzed by SDS-PAGE and immunoblotting. In 14-wk-old transgenic R6/2 mice, which show a severe disease phenotype (Labbadia et al 2011), levels of CRMP1 were significantly reduced compared to age-matched controls (Fig. 2C, D), consistent with the results from the YAC128 HD model ( Fig.…”
Section: Crmp1 Expression Levels Are Altered In Brains Of Hd Transgensupporting
confidence: 87%
“…Protein lysates were prepared from 4-, 8-, and 14-wk-old R6/2 transgenic mouse brains and wild-type controls and analyzed by SDS-PAGE and immunoblotting. In 14-wk-old transgenic R6/2 mice, which show a severe disease phenotype (Labbadia et al 2011), levels of CRMP1 were significantly reduced compared to age-matched controls (Fig. 2C, D), consistent with the results from the YAC128 HD model ( Fig.…”
Section: Crmp1 Expression Levels Are Altered In Brains Of Hd Transgensupporting
confidence: 87%
“…This phenomenon, in which an initially robust heatshock response becomes progressively impaired in polyQ diseased animals of advanced age, is thought to arise from histone hypoacetylation, resulting in a decrease in heat-shock gene transcription over time. 31 The initial increase in mouse brain and the observed increase in our patient-derived fibroblasts may represent a general response to cellular stress not specific to neurons. Cellular stress from accumulation of mutant polyQ protein is well established (reviewed in Huen et al 32 ).…”
Section: Discussionmentioning
confidence: 82%
“…Conversely, the chronic presence of aggregates can suppress the ability of cells to adequately respond to stress [48], supporting the view that protein aggregation is a major driver of the aging process. Studies in mice showed that small molecule activators of the stress response, while effective early in disease, may lose efficacy during disease progression and aging [98]. On the other hand, sustained aggregate stress may result in a disproportionate response.…”
Section: The Pn As a Target For Pharmacological Interventionmentioning
confidence: 99%